An in vitro investigation of the hepatic toxicity of PEGylated polymeric redox responsive nanoparticles. Issue 20 (27th April 2022) - Powell, Leagh G.; Alexander, Cameron; Stone, Vicki; Johnston, Helinor J.; Conte, Claudia
Abstract : PEGylated polymeric RR-NPs are less toxic than nRR-NPs. Both formulations did not have a negative impact on cell viability, but were able to elicit sub-lethal toxicity, especially in the case of non redox responsive NPs. Abstract : It can be challenging to deliver drugs to cancer cells in a targeted manner at an effective dose. Polymeric nanoparticles (NPs) are promising drug delivery systems that can be targeted to cancer cells using redox responsive elements. More specifically, intracellular and extracellular levels of the antioxidant glutathione (GSH) are elevated in cancer cells and therefore the use of NPs with a cleavable GSH-responsive element allowing these NPs to target cancer cells and trigger the release of their cargo ( e.g. anticancer drugs). The aim of this study was to assess the hepatotoxicity of polymeric NP delivery systems with and without a redox sensitive element. Copolymer poly (lactic- co -glycolic acid) (PLGA) and polyethylene glycol (PEG) NPs with (RR-NPs) and without (nRR-NPs) a redox responsive dithiylethanoate ester linker were synthesised and their toxicity assessed in vitro . As the liver is a primary site of NP accumulation, the C3A hepatocyte cell line was used to assess NP toxicity in vitro via investigation of cytotoxicity, cytokine production, genotoxicity, intracellular reactive oxygen species (ROS) production, intracellular calcium concentration, and hepatocyte function (albumin and urea production). The cellular uptake of NPs was also assessed as this may influence the cellular dose and, therefore, the cellular response. Both NPs had no detrimental impact on cell viability. However, both NPs stimulated an increase in cytokine (IL-1ra) and ROS production and decreased hepatocyte function, with the greatest effect observed for nRR-NPs. Only nRR-NPs caused DNA damage. Cells internalised both NPs and caused a (sub-lethal) increase in intracellular calcium levels. Therefore, whilst the NPs did not have a negative impact on cell viability, the NPs were able to elicit sub-lethal toxicity. By using a battery of tests we were able to demonstrate that RR-NPs may be less toxic than nRR-NPs. Our findings can therefore feed into the development of safer and more effective nanomedicines and into the design of testing strategies to assess polymeric NP safety based on knowledge of their mechanism of toxicity.